Implementation Of Integrated Learning of Islamic Religious Education to Improve Student's Social Attitude Competence - Demina; Ridwal Trisoni; Darmansyah; Hasse Jubba; Adam Mudinillah (State Islamic Institute of Madura, 2022)
This study aims to analyze the improvement of students' social attitudes through integrated learning on Islamic Religious Education subjects at MIN 1 Tanah Datar. The research method used is a quasi-experimental non-equivalent control group design. The research data was obtained using interviews and a questionnaire sheet that had been validated and then tested with the Tesmer model. Interview guidelines were distributed to four PAI teachers and a questionnaire to collect data on the social competence of 51 fourth graders. The data obtained were then analyzed using descriptive analysis to determine the percentage of students' social competence through integrated learning. This study shows a significant increase in students' social attitudes through integrated learning. Integrated learning is carried out in order to provide opportunities for students to be more active in a more inclusive learning process.